(+)-Catechin prevents methylglyoxal-induced mitochondrial dysfunction and apoptosis in EA.hy926 cells. (15th March 2017) - Zhang, Tianyu; Mu, Yingying; Yang, Mingqi; Al Maruf, Abdullah; Li, Panpan; Li, Chao; Dai, Shaohua; Lu, Jiangyi; Dong, Qiang
Abstract: Objective : To investigate whether (+)-catechin, a strong antioxidant, can prevent methylglyoxal (MGO)-induced cytotoxicity and its mechanism. Methods : Cytotoxicity, apoptosis, reactive oxygen species (ROS) generation, hydrogen peroxide (H2 O2 ) formation, mitochondrial membrane potential (MMP) and mitochondrial morphology were measured in EA.hy926 cells. Result : MGO (4 mM)-induced cytotoxicity was markedly inhibited by (+)-catechin (0.1–4 mM) in 24 h. 1 mM MGO-induced apoptotic cell death (44.7%) was significantly inhibited by 4 mM (+)-catechin (to 24.4%), 1 mM aminoguanidine (AG) (to 28.8%) or 4 mM N-acetylcysteine (NAC) (to 24.3%). (+)-Catechin (4 mM) or AG (4 mM) can inhibit the decrease of MMP induced by MGO (2–8 mM) in 3 h. (+)-Catechin (4 mM) or AG (4 mM) can inhibit MGO (4 mM)-induced mitochondrial swelling in 3 h. However, MGO (4 mM)-induced ROS and H2 O2 generation was not prevented by (+)-catechin (4 mM). Conclusions : (+)-Catechin prevents MGO-induced cytotoxicity in EA.Hy926 cells through inhibiting apoptosis and mitochondrial damage.